2016
DOI: 10.5812/ircmj.34212
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Cumin cyminum L. Plus Lime Administration on Weight Loss and Metabolic Status in Overweight Subjects: A Randomized Double-Blind Placebo-Controlled Clinical Trial

Abstract: BackgroundLimited data are available regarding the effects of combined administration of Cumin cyminum L. and lime on weight loss and metabolic profiles among subjects with overweight subjects.ObjectivesThe current study aimed to assess the effects of combined administration of Cumin cyminum L. and lime on weight loss and metabolic profiles among subjects with overweight.Patients and MethodsThis randomized double-blind placebo-controlled clinical trial was conducted on 72 subjects with overweight, aged 18 - 50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…In contrast to our results, Taghizadeh et al observed no significant difference in TAC levels in overweight subjects who took 300‐mg/day CuEO (Taghizadeh, Memarzadeh, Asemi, & Esmaillzadeh, ). These researchers in another study showed no significant effects of using C. cyminum L. plus lime (75 and 25 mg twice daily) on TAC and GSH levels in overweight subjects (Taghizadeh et al, ). ROS, which are induced by MetS, have a direct role in the initiation of oxidative stress, oxidation of lipids, formation of advanced glycation end products, and inflammation (Hopps et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to our results, Taghizadeh et al observed no significant difference in TAC levels in overweight subjects who took 300‐mg/day CuEO (Taghizadeh, Memarzadeh, Asemi, & Esmaillzadeh, ). These researchers in another study showed no significant effects of using C. cyminum L. plus lime (75 and 25 mg twice daily) on TAC and GSH levels in overweight subjects (Taghizadeh et al, ). ROS, which are induced by MetS, have a direct role in the initiation of oxidative stress, oxidation of lipids, formation of advanced glycation end products, and inflammation (Hopps et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, cumin has widely used in the treatment a wide spectrum of diseases including dyslipidemia (Srivsatava et al, ), dyspepsia (Singh et al, ), jaundice (Mnif & Aifa, ), and diarrhoea (Sowbhagya, ). Some studies have also presented that cumin may help weight loss (Taghizadeh et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…BMI reduction in high dose intake was by 0.8 kg/m 2 , while low dose intake was 0.5 kg/m 2 , and placebo only 0.1 kg/m 2 . The study concluded that high dose intake of C. cyminum with lime is beneficial for weight loss and obesity treatments [17].…”
mentioning
confidence: 99%
“…One randomized double-blind placebo-controlled clinical trial on the effect of Cumin cyminum L. plus Lime administration to observe weight loss and metabolic status in overweight subjects found that C. cyminum administered with lime may reduce body weight. C. cyminum inhibits serotonin re-uptake and increases levels of serotonin in synaptic clefts [17]. Limonene found in lime can reduce lipids by increasing lipolysis by histaminergic response and reduced appetite.…”
mentioning
confidence: 99%
See 1 more Smart Citation